Análisis macroeconómico pre y post covid-19 sobre una economía en recesión, Ecuador 2016-2021. - Matailo Pinta, Amparo Marisol; Romero Ramon, Aida Andreina (My University, 2022)
The study and monitoring of macroeconomic indicators are of vital importance and interest, since it is the statistical data that reflects the economic status of a country, even more so when they are experiencing disturbances that directly affect the economy, such as a pandemic. The objective of this research is to know the performance of the economy from 2016 to 2021 in a pre and post covid-19 pandemic scenario, analyzing the main economic indicators such as: Gross Domestic Product (GDP), Inflation, Public External Debt and Unemployment, using data from the page of the Central Bank of Ecuador. For the development of this research, the analysis of time series was carried out using the econometric software STATA 16. The results show the negative effects that the covid-19 pandemic had on an Ecuadorian economy, which already showed a recessive gap. of the economy due to the notable fiscal emergencies, even more so with the arrival of the pandemic, since it exacerbated the situation, affecting the country's macroeconomic variables and whose effect had repercussions on the quality of life of citizens.
El estudio y seguimiento de indicadores macroeconómicos son de vital importancia e interés, ya que son los datos estadísticos los que reflejan el estado económico de un país, más aún cuando estos atraviesan perturbaciones que afectan directamente a la economía como es el caso de una pandemia. El objetivo de la presente investigación es conocer el desempeño de la economía desde los años 2016 al 2021 en un escenario pre y post pandemia covid-19, analizando los principales indicadores económicos como son: Producto Interno Bruto (PIB), Inflación, Deuda Externa Pública y Desempleo, usando datas de la página del Banco Central de Ecuador. Para el desarrollo de la presente investigación se realizó el análisis de series de tiempo utilizando el software econométrico STATA 16. En los resultados se puede evidenciar los efectos negativos que tuvo la pandemia de covid-19 en una economía ecuatoriana, que ya evidenciaba una brecha recesiva de la economía debido a las notables urgencias fiscales, más aún con la llegada de la pandemia, puesto que agudizó la situación, afectando las variables macroeconómicas del país y cuyo efecto repercutió en la calidad de vida de los ciudadanos.
Keywords: ECONOMÍA EN RECESIÓN; COVID-19; INDICADORES MACROECONÓMICOS